1997
DOI: 10.1097/00001756-199707070-00025
|View full text |Cite
|
Sign up to set email alerts
|

Conditioned taste aversion and c-fos expression in the rat brainstem after administration of various USs

Abstract: Conditioned taste aversion (CTA) is a form of association learning established when an animal associates a conditioned stimulus (taste) with a subsequent unconditioned stimulus (US, illness). We have studied the relationship between the efficacy of inducing CTA to 0.1% saccharin and c-fos expression in the lower brain stem following administration of 13 different USs in rats. The effective USs were grouped into abdominal irritants, rewarding drugs and emetic agents. Regardless of the properties of USs, good co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
54
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(61 citation statements)
references
References 11 publications
7
54
0
Order By: Relevance
“…Accordingly, this activational pattern may reflect a substrate related to feeding regulation. Notably, hUcn II did not induce Fos protein in the area postrema, a chemoreceptor trigger zone for nausea where Fos is seen after diverse, malaiseinducing anorectic stimuli (Van Dijk et al, 1996;Sakai and Yamamoto, 1997;Thiele et al, 1998), and which is a critical substrate for the formation of CTAs (Sakai and Yamamoto, 1997).…”
Section: Discussionmentioning
confidence: 92%
“…Accordingly, this activational pattern may reflect a substrate related to feeding regulation. Notably, hUcn II did not induce Fos protein in the area postrema, a chemoreceptor trigger zone for nausea where Fos is seen after diverse, malaiseinducing anorectic stimuli (Van Dijk et al, 1996;Sakai and Yamamoto, 1997;Thiele et al, 1998), and which is a critical substrate for the formation of CTAs (Sakai and Yamamoto, 1997).…”
Section: Discussionmentioning
confidence: 92%
“…Both groups also exhibited unexpectedly long meals that were produced primarily by increases in the number of bursts rather than by increases in pause duration, indicating that PBN lesions did not impair Ex4-induced motivation to approach the spout. We are tempted to conclude that Ex4 effects on taste evaluation (to the extent that they exist) do not require the participation of the PBN, but it is important to note that our lesions principally targeted the LPBN with less consistent damage to the caudal medial and ventral lateral PBN subnuclei, where more gustatory-responsive neurons are present ( (Baird et al, 2001a, b;Fulwiler and Saper, 1984;Nishijo and Norgren, 1990;Sakai and Yamamoto, 1997;Tokita et al, 2012); see Figure 1b for example).…”
Section: Pbn Lesion Effects On Ex4 Hypophagiamentioning
confidence: 95%
“…Rats with PBN lesions have been reported to have attenuated sensitivity to satiating treatments, and much of the vagal input from the viscerosensitive caudal NST is relayed to the LPBN (Baird et al, 2001a;Calingasan and Ritter, 1993;Flynn et al, 1991;Karimnamazi et al, 2002). Naturally satiating and viscerally aversive stimuli have been shown to activate neurons in the LPBN as measured through c-fos reactivity (Baird et al, 2001a;Paues et al, 2006;Sakai and Yamamoto, 1997), and we have also shown that LPBN neurons exhibit in vivo electrophysiological responses to gastric distension (Baird et al, 2001a). Together, the results suggest that PBNsham rats experienced more potent visceral feedback inhibition than PBNx rats after Ex4 treatment.…”
Section: Pbn Lesion Effects On Ex4 Hypophagiamentioning
confidence: 99%
“…In CTA, the patterns of the c-fos gene expression in the brainstem nuclei, including the parabrachial nucleus (PBN), amygdala (AMY), and insular cortex (IC) induced by a taste CS and͞or a visceral US have been extensively reported (16)(17)(18)(19)(20)(21)(22)(23). However, the functional significance of the up-regulation of c-fos gene expression and Fos protein synthesis in these brain sites remains unclear.…”
mentioning
confidence: 99%